Aporphine alkaloids with in vitro antiplasmodial activity from the leaves of Phoebe tavoyana - Hanita Omar (Tanjong Malim, 2020)
Aporphine alkaloids with in vitro antiplasmodial activity from the leaves of Phoebe tavoyana by Hanita Omar